El pan de cada día y la vida eterna. Sentimiento y expresión de la religiosidad popular en los virreinatos de las Indias españolas - Bravo Guerreira, Concepción (Revista Complutense de Historia de América, 2010)
This article analyses the strategies for the adaptation of religious beliefs and practices in the Viceroyal societies of Spanish America, to the ways of life imposed upon these societies by a framework of sudden processes of change, which affected both the aborigines as well as the newcomers. The inhabitants of the Indies, just as those of the European populations of the Renaissance and Baroque periods, faced up to the necessities of daily life, always conscious that another awaited them in the afterlife. The process of making the satisfaction of the former compatible with the demands associated with the achievement of eternal good fortune stimulated the impulse of faith in the latter, and its expression in the public and private practice of devotions and rituals that marked the rhythm of earthly existence.